Emergency management of recurrent ovarian ectopic pregnancy in a hemodynamically unstable patient: A case report - Singgih, Rendy; Larose, Skmarina H.; Kwary, Meilyana MI.; Helmina, Helmina (Narra Sains Indonesia, 2025)
Recurrent ectopic pregnancy is defined as the occurrence of more than one extrauterine implantation of a fertilized ovum. Ectopic pregnancy arises when a fertilized egg fails to implant within the endometrial cavity and instead attaches to an alternative site such as the fallopian tube, ovary, or peritoneal cavity. In this report, a rare case of recurrent ovarian ectopic pregnancy in a 31-year-old patient at six weeks’ gestation is presented. The aim of this study was to highlight the clinical presentation, diagnostic challenges, and management considerations associated with recurrent ovarian ectopic pregnancy. The patient was admitted to the emergency maternal unit with severe abdominal pain. A previous history of ectopic pregnancy raised the suspicion of recurrence. The diagnosis of ectopic pregnancy was established, and the patient underwent emergency exploratory laparotomy. During the procedure, the gestational sac was identified on the surface of the right ovary. Postoperatively, the patient required blood transfusion and supportive management, and was discharged in stable condition after several days of hospitalization. Ovarian ectopic pregnancy is an uncommon but serious condition. Early diagnosis, ideally with high-resolution ultrasonography, is essential to prevent life-threatening complications such as rupture, massive intra-abdominal hemorrhage, hemorrhagic shock, and maternal mortality. This case highlights the importance for clinicians of recognizing the possibility of recurrence in patients with a prior history of ectopic pregnancy and ensuring vigilant follow-up and timely intervention.